2018
DOI: 10.1515/commun-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interaction topic and social ties on media choice and the role of four underlying mechanisms

Abstract: This study employed a scenario-based approach whereby participants were asked to choose which communication channel they prefer in certain situations. The first aim was to determine the effect of the topic of interactions and social ties on channel choice. The second aim was to examine the underlying mechanisms (controllability, anonymity, co-presence, and affective understanding) in the relation between interaction topic and social ties and channel choice. A questionnaire was administered among 238 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This outcome aligned with studies in the past that supported CMC communication format in delivering remarkable production and communication efficiency for potential creativity thinking [29,30]. Furthermore, the virtual communication environment of the CMC format offered more relaxing, anonymous, and less tense facial expression and change in tone of voice than that of FtF [13][14][15]. However, other research studies found that the performance of innovative thinking via the FtF communication format to be better than that of the CMC format, particularly in the context of education research and new product development [26][27][28]84].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This outcome aligned with studies in the past that supported CMC communication format in delivering remarkable production and communication efficiency for potential creativity thinking [29,30]. Furthermore, the virtual communication environment of the CMC format offered more relaxing, anonymous, and less tense facial expression and change in tone of voice than that of FtF [13][14][15]. However, other research studies found that the performance of innovative thinking via the FtF communication format to be better than that of the CMC format, particularly in the context of education research and new product development [26][27][28]84].…”
Section: Discussionsupporting
confidence: 82%
“…CMC communication via the virtual world is regarded as more fun, and pleasurable than FtF [15]. Croes et al [13] also suggest that selecting between FtF or CMC is significantly influenced by the perception of the user on controllability, anonymity, and co-existence. As compared to CMC, FtF communicators deliver more facial expressions and any changes in tone of voice may increase the level of tension during communication [14].…”
Section: Media Richnessmentioning
confidence: 99%
“…The stronger the communication skills in teaching, the stronger the social skills, which can reflect the teacher's social-based interpersonal attractiveness. A social appeal is a key feature of online platforms where users can enjoy interacting with others to gain shared information and benefits (Croes et al, 2018). Communication is the core of social life, and social and communication skills are closely related (Jurevičienė et al, 2012).…”
Section: Stimulus and Organism In Moocmentioning
confidence: 99%
“…Furthermore, online interactions may be even more intimate compared to offline interactions, as people are more likely to engage in intimate self-disclosure online [3]. As nonverbal cues are often lacking in online environments, individuals may feel more anonymous and safer to exchange intimate information [32]. Therefore, online communication channels might be preferred for intimate messages.…”
Section: Tie Strengthmentioning
confidence: 99%